Essays in finance: wrong-way risk, jumps and stochastic volatility - Müller, Janis (Technische Universität Dortmund, 2019)
The main focus of this thesis is about understanding the behavior of asset prices and asset returns regarding tail events, in the light of time-varying stochastic volatility and with respect to market efficiency. Thus, the contribution of this thesis is twofold: The first part deals with topics related to risk management whereas the second part deals with topics related to asset pricing. With new regulations like the credit valuation adjustment (CVA) the assessment of wrong-way risk (WWR) is of utter importance. Wrong-way risk means a negative dependence of the exposure to a counterparty on the counterparty’s credit quality. Thus, the first paper studies the co-movement of counterparty credit risk and returns of different asset classes (equity, currency, commodity and interest rate). Extreme movements in asset prices are often characterized by jumps and drying up liquidity. The second paper aims to improve the understanding of the (unconditioned) link between jumps and liquidity in chapter 3. In the third paper the dynamics of asset prices are time-changed to study the influence of stochastic volatility on asset prices in a parameter-free approach. Applying the time-changing technique avoids to use a specific process for volatility to study the impact of stochastic volatility on asset prices. Firstly, formulas for the expected return of assets and the risk-free rate are derived. It is noteworthy that the risk-free rate becomes stochastic under the time-change. Based on the theoretical findings, stochastic consumption volatility is explored considering prevailing puzzles. Secondly, a factor is constructed mimicking the effect of stochastic volatility of the market portfolio on asset prices extending the five-factor model of Fama and French (2015). Considering anomalies targeted by existing factor models, the constructed factor especially helps to describe cross-sectional excess returns of portfolios formed on size and momentum. This finding indicates that the momentum effect is partly explicable by stochastic volatility. The fourth paper deals with ambiguous volatility as an explanation for time-variation in the market’s risk premium. Finally, the fifth paper is about the currently discussed topic of market efficiency regarding cryptocurrencies. Using three delay measures as given in Hou and Moskowitz (2005) it is shown that news, affecting the cryptocurrency market, are much faster incorporated in prices during the last three years indicating that the cryptocurrency market becomes more efficient over time. Furthermore, the price delay is mainly driven by liquidity which is studied in the cross-section of 75 cryptocurrencies.
Keywords: Risk management; Asset pricing; 330; Kreditmarkt; Risikomanagement